The Mitochondrial Voltage-Dependent Anion Channel 1, Ca2+ Transport, Apoptosis, and Their Regulation - Shoshan-Barmatz, Varda; De, Soumasree; Meir, Alon (Frontiers in Oncology, 2017)
In the outer mitochondrial membrane, the voltage-dependent anion channel 1 (VDAC1) functions in cellular Ca2+ homeostasis by mediating the transport of Ca2+ in and out of mitochondria. VDAC1 is highly Ca2+-permeable and modulates Ca2+ access to the mitochondrial intermembrane space. Intramitochondrial Ca2+ controls energy metabolism by enhancing the rate of NADH production via modulating critical enzymes in the tricarboxylic acid cycle and fatty acid oxidation. Mitochondrial [Ca2+] is regarded as an important determinant of cell sensitivity to apoptotic stimuli and was proposed to act as a “priming signal,” sensitizing the organelle and promoting the release of pro-apoptotic proteins. However, the precise mechanism by which intracellular Ca2+ ([Ca2+]i) mediates apoptosis is not known. Here, we review the roles of VDAC1 in mitochondrial Ca2+ homeostasis and in apoptosis. Accumulated evidence shows that apoptosis-inducing agents act by increasing [Ca2+]i and that this, in turn, augments VDAC1 expression levels. Thus, a new concept of how increased [Ca2+]i activates apoptosis is postulated. Specifically, increased [Ca2+]i enhances VDAC1 expression levels, followed by VDAC1 oligomerization, cytochrome c release, and subsequently apoptosis. Evidence supporting this new model suggesting that upregulation of VDAC1 expression constitutes a major mechanism by which apoptotic stimuli induce apoptosis with VDAC1 oligomerization being a molecular focal point in apoptosis regulation is presented. A new proposed mechanism of pro-apoptotic drug action, namely Ca2+-dependent enhancement of VDAC1 expression, provides a platform for developing a new class of anticancer drugs modulating VDAC1 levels via the promoter and for overcoming the resistance of cancer cells to chemotherapy.